Public food procurement: a transformative instrument for sustainable food systems - Stein, Mark; Hunter, Danny; Swensson, Luana; Schneider, Sergio; Tartanac, Florence (MDPI, 2022)
Public food procurement policies and initiatives designed to use government purchasing power and regular demand for food have gained much global attention in the last decade. Public food procurement policies can be used to promote healthy diets, based on sustainable food systems, in workplaces, schools, universities, hospitals, aged care facilities, and other venues at which public meals are provided. A key characteristic of public food procurement is that it offers the opportunity to determine the way food is procured in addition to what type of food is purchased (local, diverse, nutritious, healthy, culturally appropriate, etc.), from whom (smallholder farmers, small and medium food enterprises, women, youth, and/or other vulnerable groups), and from which type of production (from agroecology or organic or other modes of agricultural production that ensure environmental sustainability as well as biodiversity). In this Special Issue, we solicited a range of articles from academics, researchers, and practitioners exploring innovative approaches and methods in the field of sustainable public food procurement practice and policy, with a particular focus on the use of public food procurement policies as an instrument to promote environmental sustainability and possible means by which to measure its impacts, areas in which research is currently lacking. This Special Issue comprises two academic literature reviews and three case studies—from Italy, Kenya, and South Africa.